Pre-mandibular pharyngeal pouches in early non-teleost fish embryos - Horackova, Agata; Pospisilova, Anna; Stundl, Jan; Minarik, Martin; Jandzik, David; Cerny, Robert (Proceedings. Biological sciences, 2023)
The vertebrate pharynx is a key embryonic structure with crucial importance for the metameric organization of the head and face. The pharynx is primarily built upon progressive formation of paired pharyngeal pouches that typically develop in post-oral (mandibular, hyoid and branchial) domains. However, in the early embryos of non-teleost fishes, we have previously identified pharyngeal pouch-like outpocketings also in the pre-oral domain of the cranial endoderm. This pre-oral gut (POG) forms by early pouching of the primitive gut cavity, followed by the sequential formation of typical (post-oral) pharyngeal pouches. Here, we tested the pharyngeal nature of the POG by analysing expression patterns of selected core pharyngeal regulatory network genes in bichir and sturgeon embryos. Our comparison revealed generally shared expression patterns, including Shh, Pax9, Tbx1, Eya1, Six1, Ripply3 or Fgf8, between early POG and post-oral pharyngeal pouches. POG thus shares pharyngeal pouch-like morphogenesis and a gene expression profile with pharyngeal pouches and can be regarded as a pre-mandibular pharyngeal pouch. We further suggest that pre-mandibular pharyngeal pouches represent a plesiomorphic vertebrate trait inherited from our ancestor's pharyngeal metameric organization, which is incorporated in the early formation of the pre-chordal plate of vertebrate embryos.
Keywords: evolution; os hyoideum; Animals; pharyngeal pouch; mouth; Skull; pharynx; lebka; Morphogenesis; mandibula; morfogeneze; zvířata; Hyoid Bone; vertebrate head; pre-oral gut; Mandible